2007
DOI: 10.1002/smll.200700120
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐Controlled Synthesis of CdSe Tetrapods Using Cationic Surfactant Ligands

Abstract: Keeping in shape: Quaternary alkylammonium compounds promote the formation of faceted quantum dots. Their use in hot‐injection synthesis chemistry provides a new means to form uniform CdSe tetrapods without a selective precipitation step (see picture; TOPSe: trioctylphosphine selenide), and introduces the prospect of nanoparticle shape control through ligand–nanoparticle charge interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 46 publications
2
93
1
Order By: Relevance
“…In particular, tetrapod-shaped CdTe nanocrystals were synthesized with high shape selectivity and high size uniformity (Zhang & Yu, 2006). In contrast to this, CdSe nanocrystals were relatively hard to synthesize with high shape selectivity, since the energy difference between the wurzite and the zinc blende is too small to facilitate tetrapod-shaped crystals (Zhang & Yu, 2006;Asokan et al, 2007). Recently, Asokan et al reported synthesis of CdSe tetrapods with high shape selectivity and high size uniformity (Asokan et al, 2007).…”
Section: Tailoring the Morphology Of Cdse Nanocrystals By Alloying Wimentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, tetrapod-shaped CdTe nanocrystals were synthesized with high shape selectivity and high size uniformity (Zhang & Yu, 2006). In contrast to this, CdSe nanocrystals were relatively hard to synthesize with high shape selectivity, since the energy difference between the wurzite and the zinc blende is too small to facilitate tetrapod-shaped crystals (Zhang & Yu, 2006;Asokan et al, 2007). Recently, Asokan et al reported synthesis of CdSe tetrapods with high shape selectivity and high size uniformity (Asokan et al, 2007).…”
Section: Tailoring the Morphology Of Cdse Nanocrystals By Alloying Wimentioning
confidence: 99%
“…In contrast to this, CdSe nanocrystals were relatively hard to synthesize with high shape selectivity, since the energy difference between the wurzite and the zinc blende is too small to facilitate tetrapod-shaped crystals (Zhang & Yu, 2006;Asokan et al, 2007). Recently, Asokan et al reported synthesis of CdSe tetrapods with high shape selectivity and high size uniformity (Asokan et al, 2007). Most of syntheses of anisotropic CdSe nanocrystals involve special surfactants such as alkylphosphonic acid, quaternary ammonium salt compounds, etc.…”
Section: Tailoring the Morphology Of Cdse Nanocrystals By Alloying Wimentioning
confidence: 99%
“…6,7 The preference of using TPs over QDs and NRs is due to the overall higher surface area to volume ratio which leads to more electrically desirable and connected paths, thus better electrical transport. [8][9][10][11][12] Although it is difficult to synthesize more complex nanostructures reproducibly, recent advances have demonstrated low-cost chemical synthesis of TPs with high yields in shape selectivity and dimensional uniformity using surfactant cationic ligands. 11 Capitalizing on such advances, we investigate the impact of using two different sizes of cadmium selenide (CdSe) TPs on device performance along with the respective nano-scale morphology of the hybrid CdSe TPs:poly (3-hexylthiophene) (P3HT) layer.…”
mentioning
confidence: 99%
“…11 Oleic acid (OA) used in the synthesis binds to the TP surface as a surface ligand coating, giving the TPs stability towards chemical degradation and enhancing colloidal stability in organic solvents. However, due to relatively long length of OA ($2 nm), such ligands must be exchanged with shorter ones in order to reduce the inter-particle distances, thereby enhancing the electronic transport of the resulting thin layer incorporating the TPs.…”
mentioning
confidence: 99%
“…The synthesis of cadmium chalcogenide nanoparticles has reached a high degree of sophistication: impressive levels of control over shape and size have been reported for cadmium chalcogenide nanodots, nanorods and branched structures. [1][2][3][4] The ability to order nanorods in particular orientations will present unique opportunities for the nanorods of a specic chemical composition to be used in a wide variety of different applications. For example, nanorods which in an out-of-plane orientation are suitable for photovoltaic/diode applications could be used in eld effect transistors when ordered in-plane between two electrodes.…”
Section: Introductionmentioning
confidence: 99%